Aerial Photo Utilization in Estimating Suspended Sediment in the Wuryantoro Watershed, Wonogiri - Sugiharto Budi Santoso; Kuswaji Dwi Priyono; Alif Noor Anna (Forum Geografi, 2003)
Suspended sediment load flowing out from a watershed is normally predicated by analysis os suspended sediment of water sample, and the volume of suspended sediment be calculated based on sediment concentration and river discharge. Such field measurements need a lot of field data and they are time consuming. Another method for prediction of suspended sediment by using remote sensing imagery data and recorded rainfall data. The objective of this research is to 1) examine the capability of remote sensing technique to obtain the parameters of the physical data of land in the prediction of suspended sediment; 2) examine the accuracy of the model for prediction suspended sediment. This research is carried out in Wuryantoro watershed, Wonogiri. The main data to obtain the parameters of the physical data of land is infrared aerial photograph on scale 1 : 10.000. the method that used in this research is interpretation of remote sensing imagery data, combined with rainfall data. The result show that the accuracy of landuse is 88.5%, the accuracy of slope is 87.67%. the accuracy of the prediction of suspended sediment by model A3 87.07%, model C1 86.63%, model C2 90.57%, model A8 84.13%, model A9 80.1%, and model C4 78.6%.